Synchronous eyelid oncocytoma and conjunctival intraepithelial neoplasia - Zachariah Chowdhury; Benjamin Nongrum; Chandana Rajbongshi (University of São Paulo, 2021)
Oncocytoma of the eyelid is a rare neoplasm. Oncocytoma associated with an ocular surface squamous neoplasm, namely conjunctival intraepithelial neoplasia, is very hard to find in the literature. Herein we report a case of a 53-year-old male who presented with a swelling in the right lower lid over the last 6 years, along with a growth in the conjunctiva of the same eye for the last 2 years and encroaching upon the cornea for the last 4 months. Excision biopsy of the lower lid mass showed histopathological features consistent with oncocytoma. The conjunctival tissue revealed conjunctival intraepithelial neoplasia 3 (severe dysplasia). This case documents a rare synchronous dual ocular neoplasia, a very unlikely coexistence of oncocytoma with conjunctival intraepithelial neoplasia.